2020
DOI: 10.3390/molecules25133015
|View full text |Cite
|
Sign up to set email alerts
|

Insights on the Larvicidal Mechanism of Action of Fractions and Compounds from Aerial Parts of Helicteres velutina K. Schum against Aedes aegypti L.

Abstract: Viral diseases transmitted by the female Aedes aegypti L. are considered a major public health problem. The aerial parts of Helicteres velutina K. Schum (Sterculiaceae) have demonstrated potential insecticidal and larvicidal activity against this vector. The objective of this research was to investigate the mechanisms of action involved in the larvicidal activity of this species. The cytotoxicity activity of H. velutina fractions and compounds of crude ethanolic extract of the aerial parts of this spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…These authors [ 62 ] have demonstrated that exposure of Aedes larvae to Schinus terebinthifolius extract results in the disorganization of the larval midgut epithelium, which might be attributed to the accumulation of the extract in the larval midgut. Reports indicate that this phenomenon can be attributed to the high permeability of the larval peritrophic membrane [ 63 ]. The discoloration of RHA-treated larvae ( Fig 1 ) may be a consequence of the interaction of insecticidal compounds from extract with larvae cuticle chitin, as suggested by De Araújo et al [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…These authors [ 62 ] have demonstrated that exposure of Aedes larvae to Schinus terebinthifolius extract results in the disorganization of the larval midgut epithelium, which might be attributed to the accumulation of the extract in the larval midgut. Reports indicate that this phenomenon can be attributed to the high permeability of the larval peritrophic membrane [ 63 ]. The discoloration of RHA-treated larvae ( Fig 1 ) may be a consequence of the interaction of insecticidal compounds from extract with larvae cuticle chitin, as suggested by De Araújo et al [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…A few of these substances (tiliroside and 7,4'-di-O-methyl-8-O-sulfate flavone) are known to possess activity against Ae. aegypti larvae (Fernandes et al, 2019;Fernandes et al, 2020b), and these results have triggered interest with respect to studying other stages of the vector life cycle. The development of resistance in insects to common insecticides is a major problem.…”
Section: Discussionmentioning
confidence: 99%
“…The hexane and dichloromethane fractions as well as two flavonoids isolated from the dichloromethane fraction: (1) 7,4'-di-O-methyl-8-O-sulfated flavone (sulfated flavonoid) and (2) Tiliroside (glycosidic flavonoid) (Figure 1) (Fernandes et al, 2019;Fernandes et al, 2020b) showed promising larvicidal activity against Ae. aegypti.…”
Section: Plant Materials and Test Substancesmentioning
confidence: 99%
See 1 more Smart Citation
“…Monoterpenes and sesquiterpenes are the most prevalent chemicals in the largest class of terpenoids found in natural plant products (Dubey et al, 2003). Thymol (5-methyl-2-(1methylethylphenol), a monoterpene that is present in thyme and oregano essential oils (Budavari, 1989), is notable for its antibacterial, antifungal, anti-inflammatory, anticancer, and insecticide properties (Guimares et al, 2012;Yin et al, 2012) (Figure 1).…”
Section: Introductionmentioning
confidence: 99%